Respuesta :
we have that
0 = –2x²+ 2x + 3
0 = –2x²+ 2x + 3
Group terms that contain the same variable, and move the constant to the opposite side of the equation
(–2x²+ 2x)=-3
Factor the leading coefficient
-2*(x²-x)=-3
Complete the square. Remember to balance the equation by adding the same constants to each side
-2*(x²-x+0.25)=-3-0.50
Rewrite as perfect squares
-2*(x-0.5)²=-3.50
(x-0.5)²=-3.50/-2
(x-0.5)²=1.75------> square root both sides
(+/-)(x-0.5)=√7/2
(+)(x-0.5)=√7/2----> (√7/2)+0.5----> x=1.823
(-)(x-0.5)=√5/2-----> x=0.5-(√7/2)----> x=-0.823
the solutions are
x=1.823
x=-0.823